Pengaruh Keluarga Dalam Pemerolehan Bahasa kedua Pada anak usia 1.5 tahun: Sebuah Analisis Teori Monitor Krashen - Rendy Pribadi; Zainal Rafli; Ninuk Lustyantie (Universitas Indraprasta PGRI, 2019)
Abstract: The object of this research is to describe and comprehensively understand cognition in second language acquisition in children aged 1; 5 years: a formal approach to the type of Krashen monitor theory. The method in this study uses a qualitative approach. Qualitative because based on taking a historical data in the form of observation and recording using electronic media as a recorder of speech forms.Data is collected through data collection by recording and then recording one word and two words from the child's speech then describing it syntactically the words that the child uttered. The method used is observation and conversation by asking a few questions. The object in this study was a child named Raffasya Wirayudha who was 1; 5 years old.. The findings in this study were to test the development of second language acquisition with the type of monitor theory. The model theory is applied in children aged 1, 5 years who have a first language (Sundanese) and a second language (Indonesian). So that we can know the level of mastery of each language with the type of monitor model. The findings are: 1. Language acquisition and learning can be carried out in the family sphere, 2. The development of B2 language learning is more interactive if using media, and 3. Language problems can be solved if it gives the child the opportunity to talk and control unstable emotions in the speakers when speaking.